Meditation treatment of Alzheimer disease and mild cognitive impairment: A protocol for systematic review. Issue 10 (March 2020) - Chen, Yunhui; Zhang, Jiayuan; Zhang, Tiane; Cao, Liu; You, Yanyan; Zhang, Chunjiang; Liu, Xinglong; Zhang, Qi
Abstract: Background: Growing body of scientific researches in recent years have suggested the promising effect of meditation on improving cognitive impairment of Alzheimer disease (AD) and mild cognitive impairment (MCI). This paper aims to provide a protocol for systematic review to evaluate the efficacy of meditation on cognition performance of patient with AD and MCI. Methods: The Cochrane Library, PubMed, EMBASE, Web of Science, the Chinese Biological Medicine Database, China National Knowledge Infrastructure, Wanfang database, and VIP information database will be searched systematically and electronically from establishment to March 2020. All published randomized controlled trials related will be included. Assessment of bias risk and data analyses will be implemented by Review Manager (V.5.3.5). The strength of the evidence will be assessed by the Grading of Recommendations Assessment, Development and Evaluation system. Results: A high-quality synthesis of current evidence of meditation for patient with AD and mild cognitive impairment will be provided in this study. Conclusion: This protocol of systematic review will be helpful for providing evidence of whether meditation is an effective and safe intervention for cognitive impairment of patient with AD and MCI. Ethics and dissemination: Ethical approval is unnecessary since this protocol is only for systematic review and does not involve privacy data or conduct an animal experiment. This protocol will be disseminated by a peer-review journal or conference presentation. Systematic review registration: PROSPERO CRD42019145932.